The comics grid ([Comics grid], 2011)
"The Comics Grid is a collaborative, peer-edited online academic journal dedicated to comics scholarship. Its purpose is to make original contributions to the field of comics scholarship and to advance the appreciation of comic art within academia and the general cultural mediascape. This journal seeks to function as an online laboratory where different critical approaches to comics are publicly and collectively put to test. Though our scope wants to be as diverse as possible, our initial aim is to focus on the analysis of specific comics page layouts and panels."
Keywords: Comic books, strips, etc : History and criticism : Periodicals; Graphic novels : History and criticism : Periodicals; Comic books, strips, etc; Graphic novels